Monuments of early east slav-serbian literary relations as sources for studying serbian identity - Jelesijević, Snežana (Sociološki pregled, 2025)
A larger segment of this paper is dedicated to the presentation of the major results of studying Saint Sava’s Nomocanon to date, including the data about Serbian-Slavic transcripts, Serbian abridged version of the Old Church Slavonic language and examples of Moscow printed Krmčija in Serbian collections from 1649 to 1653. A brief overview is given of the observed traces of the application of Nomocanon and its impact on the life and consciousness of the Serbs in the Middle Ages. An important place among them is held by the realization of the idea of the symphony between the Church and the state, and their cooperation in regulating marital relations. The author thinks that Saint Sava’s personality and acting, as well as Nomocanon within it, contributed to the formation of Serbian identity. The author looks at the importance of Saint Sava’s Žiča Sermon on the True Faith, and the Synodicon of Orthodoxy, while drawing attention to the necessity of studying Serbian transcripts of the Pandects of Nikon of the Black Mountain.
Keywords: Nomocanon; Saint Sava; Sermon on the True Faith; Synodicon of Orthodoxy; Pandects of Nikon of the Black